2020
DOI: 10.1159/000508393
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Uveal Melanoma

Abstract: Introduction: Multiple uveal melanoma is a rare occurrence and includes bilateral melanoma, unilateral multiple/multifocal melanoma, or melanoma with metastasis to the ipsilateral or contralateral eye. Methods: A chart review of patients diagnosed with uveal melanoma between January 2013 and January 2019 at the Duke University Eye Center Ophthalmic Oncology Service was performed. Results: Three patients with multiple, sequential melanoma were identified; patient 1 had bilateral choroidal melanoma and patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They were excluded if they had metastatic disease at presentation or if they had multiple uveal melanomas, which were previously reported in a case series by Kheir et al. 17 Relevant information consisting of patient demographics, tumor characteristics, treatment data, eye plaque characteristics, oncologic outcomes (local control and distant metastasis), VA, and radiation-related toxicity data were abstracted from the electronic medical record (Maestro/EPIC and ARIA RadONC).…”
Section: Methodsmentioning
confidence: 99%
“…They were excluded if they had metastatic disease at presentation or if they had multiple uveal melanomas, which were previously reported in a case series by Kheir et al. 17 Relevant information consisting of patient demographics, tumor characteristics, treatment data, eye plaque characteristics, oncologic outcomes (local control and distant metastasis), VA, and radiation-related toxicity data were abstracted from the electronic medical record (Maestro/EPIC and ARIA RadONC).…”
Section: Methodsmentioning
confidence: 99%
“…One published retrospective study found the metastasis-related mortality rate of patients with primary uveal melanoma associated with ocular melanocytosis to be substantially higher than that of patients with similar tumors not associated with this condition [3]. A few case series have described 2 independent melanomas associated with ocular melanocytosis [4][5][6][7][8], and 1 case of 3 independent melanomas in the context of oculodermal melanocytosis has been reported [9]. As a result, patients with ocular melanocytosis are routinely screened for the development of uveal melanoma.…”
Section: Introductionmentioning
confidence: 99%